S34 The effects of a novel formulation of inhaled cromolyn sodium (pa101) in idiopathic pulmonary fibrosis and chronic cough: a randomised, controlled, phase 2 trial. (15th November 2017) - Brring, SS; Wijsenbeek, MS; Agrawal, S; den Berg, JWK van; Stone, H; Maher, TM; Tutuncu, A; Morice, AH
Abstract : Introduction and Objectives: Cough can be a debilitating symptom of idiopathic pulmonary fibrosis (IPF). The efficacy and safety of inhaled PA101, a novel formulation of cromolyn sodium was investigated in IPF patients with chronic cough in a multi–centre, randomised, double-blind, placebo-controlled, 2-cohort, 2-period, cross-over trial. To explore the mechanism of anti-tussive activity of PA101, a parallel study of similar design was conducted in patients with chronic idiopathic cough (CIC). Methods: Twenty-four participants with IPF and chronic cough were randomised to receive PA101 (40 mg) or matching placebo three times a day for 2 weeks, followed by 2 weeks wash out, and then crossed over. The primary outcome measure was objective daytime cough frequency (from 24 hour acoustic recording, Leicester Cough Monitor) and secondary outcomes included subjective cough–specific quality of life (LCQ) assessed at Day 14. The primary efficacy analysis was based on a mixed effects model. In the CIC cohort, twenty-eight participants were randomised in a study with similar design and endpoints. Results: In IPF patients, PA101 reduced daytime cough frequency by 31.1% at day 14 compared to placebo. Daytime cough frequency decreased from a mean(SD) of 55(55) to 39(29) coughs/hour at day 14 with PA101 versus 51(37) to 52(40) coughs/hour following placebo (figure 1 ). There was a significant correlation coefficient between change in cough severity (VAS score) and change in daytime cough frequency with PA101 at Day 14, r=0.415 (p=0.048). There was a trend towards improvement in LCQ score with PA101 compared to placebo; mean treatment difference 1.1, p=0.09. PA101 was associated with an improvement in chest symptom and psychological domains of the KBILD-QOL (p<0.05). In contrast, no treatment benefit for PA101 was observed in the CIC cohort; mean reduction of daytime cough frequency at Day 14 for PA101 adjusted for placebo was 6.2%. PA101 was well tolerated in both cohorts and the incidence of adverse events was comparable between PA101 and placebo treatments. Conclusions: This study suggests that the mechanism of cough in IPF may be disease specific. Inhaled PA101 may be a treatment option for chronic cough in patients with IPF and warrants further investigation.